2020
DOI: 10.1101/2020.07.24.220566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiological foundations of the human default-mode network revealed by brain-wide intracranial-EEG recordings during resting-state and cognition

Abstract: Investigations using noninvasive functional magnetic resonance imaging (fMRI) have provided significant insights into the unique functional organization and profound importance of the human default mode network (DMN), yet these methods are limited in their ability to resolve network dynamics across multiple timescales. Electrophysiological techniques are critical to address these challenges, yet few studies have explored the neurophysiological underpinnings of the DMN. Here we investigate the brain-wide electr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…Another mechanism could potentially be that in the stronger current density under the central reference electrode location with reversed polarity might have enabled a de‐coupling of default‐mode network hubs over central areas with the fronto‐parietal working memory network. The default mode network has been associated with slow frequency coherence in the delta to alpha range (Das et al, 2020; Kim et al, 2014; Samogin et al, 2019), and more specifically, areas of the default‐mode and fronto‐parietal network have been shown to be related to theta band connectivity (Kam et al, 2019). This might also explain the absence of a modulation of response times during in‐phase tACS in our study, where we used the larger return electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism could potentially be that in the stronger current density under the central reference electrode location with reversed polarity might have enabled a de‐coupling of default‐mode network hubs over central areas with the fronto‐parietal working memory network. The default mode network has been associated with slow frequency coherence in the delta to alpha range (Das et al, 2020; Kim et al, 2014; Samogin et al, 2019), and more specifically, areas of the default‐mode and fronto‐parietal network have been shown to be related to theta band connectivity (Kam et al, 2019). This might also explain the absence of a modulation of response times during in‐phase tACS in our study, where we used the larger return electrode.…”
Section: Discussionmentioning
confidence: 99%
“…If so, slow‐4 might provide more information about the dynamics of DMN, supporting that DMN has frequency‐specific properties (Park et al, 2019 ). Nevertheless, future study is needed to investigate the electrophysiological foundation of DMN (Das et al, 2020 ; Samogin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anup Das, de los Angeles, & Menon, 2020). Electrodes in temporal regions, such as superior temporal sulcus (STS) and middle temporal gyrus (MTG) consisted most of the DMN electrodes included in their study, which is highly different from our study as we focus more in medial prefrontal cortex (mPFC) and posterior cingulate cortex (PCC).…”
Section: Frequency Specific Phase Synchronizationmentioning
confidence: 73%
“…Our results suggest the active theta coupling of the DMN at rest, which may contribute to maintenance of the memory function. Interestingly, a recent study observed greater intra-DMN phase synchronization in the slow-wave (<4Hz) while greater cross-network interaction of the DMN in higher frequencies (>4Hz; Anup Das, de los Angeles, & Menon, 2020). Electrodes in temporal regions, such as superior temporal sulcus (STS) and middle temporal gyrus (MTG) consisted most of the DMN electrodes included in their study, which is highly different from our study as we focus more in medial prefrontal cortex (mPFC) and posterior cingulate cortex (PCC).…”
Section: Discussionmentioning
confidence: 92%